Kayumanggi - Magpile, Christine Marie Lim (Lampara books, 2013)
"A puppy is adopted by a young boy, Pepe, who names his "Kolate." With the passage of time, both the young boy and the puppy grow up and mature. Then comes an event which in time became an important event in Philippine history."